Learning Speaking Skills at the Mamba'ul Ma'arif Islamic Boarding School in Denanyar Jombang from the Perspective of Nasir Abdul Ghalli and Abdul Hamid Abdullah - Moh Rifqi Falah Al Farabi; Ahmad Mubaligh; M. Faisol (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the learning of speaking skills at the Mamba’ul Ma’arif Denanyar Jombang Islamic boarding school from the perspective of Nasir Abdul Ghalli and Abdul Hamid Abdullah. This study aims to examine the learning of speaking skills through the book Al-Hiwar Bayna Yadayk, from the perspectives of Nasir Abdul Ghalli and Abdul Hamid Abdullah, and to identify its advantages. This study uses a qualitative case study approach. The study’s subjects were speaking skills teachers, male class XI students, and male dormitory supervisors. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana models. The results of the study indicate that: 1) speaking skills learning takes place in accordance with the learning principles of Nasir Abdul Ghalli and Abdul Hamid Abdullah. 2) The advantages of the book Al Hiwar Bayna Yadayk are the use of language that is easy to understand, a relatively simple sentence structure (tarkib), material that is relevant to learning needs, each chapter contains new vocabulary (mufradat), and the vocabulary presented is applicable and can be used in everyday communication